Profile of blood donors who presented adverse reactions to the donation - Melissa Orlandi Honório Locks; Nádia Chiodelli Salum; Beatriz Steingreber de Barros; Eliane Matos; Jane Cristina Anders; Dulcinéia Ghizoni Schneider
ABSTRACT Objective: identify the adverse reactions presented by blood donors and outline their sociodemographic profile. Method: a quantitative, cross-sectional retrospective study of 780 records of blood donors from a public hemocenter in the southern region of Brazil, from December 2015 to January 2016. For the analysis the descriptive statistics was used. Results: it was identified that throughout 12 months, the total blood donors corresponded to 27,300 people, in which 780 developed at least one reaction. They were characterized by female and recurrent donors, single, with a complete average level of education, ranging from 16 to 30 years, who triggered between 1 and 3 reactions. Mild reactions were more frequent, followed by moderate and severe reactions. Conclusion: There is a high rate of adverse reactions from donors emphasizing the need for changes in hemotherapy care practices.